1996
DOI: 10.2135/cropsci1996.0011183x003600030019x
|View full text |Cite
|
Sign up to set email alerts
|

Cotton Response to Seasonal Patterns of Flower Removal: I. Yield and Fiber Quality

Abstract: Cotton (Gossypium hirsutum L.) yield and quality can be affected by altered fruiting patterns related to the abscission of fruiting forms. This field study quantified the effects of flower removal during various stages of reproductive development on subsequent yield development, boll development, and fiber properties. Effects of early‐, mid‐, and late‐season flower loss on cotton reproductive development was determined. Various flower removal treatments were imposed on two cultivars at Clayton, NC, during 1991… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…In contrast, a similar level and timing of damage imposed on crops grown in Narrabri resulted in recovery in yield not signiÞcantly different to (but ranked lower) than the control (Sadras 1996a). Similarly, removal of large squares during early fruiting by Ungar et al (1987) in Israel and Jones et al (1996a) in North Carolina resulted in yield recovery equal to the control. We therefore conclude that cotton crops grown during tropical winter of northern Australia should be more tolerant of early fruit loss than those grown during temperate summer.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, a similar level and timing of damage imposed on crops grown in Narrabri resulted in recovery in yield not signiÞcantly different to (but ranked lower) than the control (Sadras 1996a). Similarly, removal of large squares during early fruiting by Ungar et al (1987) in Israel and Jones et al (1996a) in North Carolina resulted in yield recovery equal to the control. We therefore conclude that cotton crops grown during tropical winter of northern Australia should be more tolerant of early fruit loss than those grown during temperate summer.…”
Section: Discussionmentioning
confidence: 90%
“…Kletter and Wallach (1982) removed small squares (four per plant), large squares (four per plant), and bolls (two per plant) during three time periods with no effect on lint yield. Similarly, Jones et al (1996) found that removing all ßowers at the fourth week of ßowering or later decreased lint yields. Fife (2000) found yield decreases when 100% of squares were removed during the Þrst 4 wk of ßowering, but that lesser (up to 75%) removal levels did not affect lint yield.…”
mentioning
confidence: 80%
“…Ungar et al (1987) found little yield response to square removal or to the removal of small bolls, but decreased yields when large bolls were removed. Retention of bolls that would have been abscised under normal conditions can make up for other bolls lost within a few days of ßowering (Jones et al 1996). Bolls that have developed for 15Ð18 d after ßower opening generally will not abscise from the plant although yield losses may still occur because of feeding by H. zea (Guinn 1982, Gore et al 2000a.…”
mentioning
confidence: 99%
“…Removing fruiting forms usually enhances vegetative growth and development, such as increased plant height, total dry weight, leaf area index (LAI), and lengthening of anthesis (Ungar et al, 1987;Jones et al, 1996). Removing early-season flower buds increased root growth, while removing fruiting branches alters spatial yield distribution (Sadras, 1995;Bednarz and Roberts, 2001;Dumka et al, 2004).…”
Section: Removal Of Early Fruiting Branches And/or Floral Budmentioning
confidence: 99%